The Role and Applications of Artificial Intelligence Approaches in The Health Field: A Literature Review (International Journal of Engineering and Computer Science, 2025)
Since the emergence of the Corona pandemic, physical social distancing, wearing masks, sterilizing and washing hands, and regularly testing temperatures have become important solutions to avoid the risk of infection with the Corona virus. But the presence of weakness in health care systems, overcrowding, and the system of community behavior is the main challenge during the pandemic period. Despite the prevention methods and restrictions on travel, the virus has spread widely in all countries of the world, so it is necessary to consider the role of medical technologies with the emergency situation. global health systems. AI, cloud computing, big data and robotics have an essential role in the health system. AI is an important technology that has a major role in various fields. This study highlights the most important current research and proposed models on the role and applications of AI to confront the Corona pandemic. The main objective of this research paper is to discuss four of the core issues, methods and algorithms used within the field of AI to fight the Corona pandemic, which are: early detection and diagnosis, prediction of the spread of the Corona virus and disease outbreaks, drug discovery, and vaccine development. This study examines in depth these controversial research topics to reach an accurate and concise conclusion. Thus, this study makes important recommendations regarding future research directions related to AI’s applications.